The African American almanac - Narins, Brigham 1962-.; Gale Group (Detroit, Mich. Gale, 2008)
Provides a range of historical and current information on African American history, society and culture. Includes coverage of such topics as: Africa and the Black diaspora; film and television; landmarks; national organizations; population; religion; science and technology; and sports.
Chronology -- African American firsts -- Significant documents in African American history -- African American landmarks -- Africa and the African diaspora -- Africans in America: 1600 to 1900 -- Civil rights -- Black nationalism -- National organizations -- Law -- Politics -- Population -- Employment and income -- Entrepreneurship -- Family and health -- Education -- Religion -- Literature -- Media -- Film and television -- Drama, comedy, and dance -- Classical music -- Sacred music traditions -- Blues and jazz -- Popular music -- Visual and applied arts -- Science and technology -- Sports -- Military -- Appendix.
"Formerly the Negro Almanac."
Electronic reproduction.
Keywords: African Americans -- Encyclopedias; African Americans -- History; African Americans -- Civil rights; African Americans -- Economic conditions; African Americans -- Education; African Americans -- Music; African Americans -- Politics and government; African Americans -- Religion; African Americans -- Social conditions; African Americans -- Societies, etc; American literature -- African American authors; Electronic books